LIM‐only protein FHL2 regulates experimental pulmonary Schistosoma mansoni egg granuloma formation. Issue 11 (13th September 2015) - Kurakula, Kondababu; Vos, Mariska; van Eijk, Marco; Smits, Hermelijn H.; de Vries, Carlie J.M.
Abstract : LIM‐only protein FHL2 is associated with several immune and inflammatory diseases such as arthritis, influenza A virus infection, and lung inflammation. However, the role of FHL2 in macrophage differentiation and in the development of granuloma formation is unknown. Here, we show that expression of FHL2 is induced in mouse bone marrow derived macrophages (BMMs) following stimulation with M2 cytokines such as IL‐4 and IL‐10. FHL2‐knockout (FHL2‐KO) BMMs exhibit a proinflammatory M1 phenotype after LPS treatment and display a reduced anti‐inflammatory M2 phenotype following IL‐4 treatment. Furthermore, thioglycollate‐induced migration of macrophages and B cells is enhanced in FHL2‐KO mice. To evaluate the importance of FHL2 in the development of pulmonary granuloma formation, FHL2‐KO mice were challenged with Schistosoma mansoni eggs. FHL2‐KO mice show an enhanced number of granulomas and display decreased expression of Th2 markers and an exacerbated Th1 type of inflammation, characterized by enhanced expression of neutrophil markers and Th1 cytokines. Furthermore, the expression of barrier proteins is reduced in FHL2‐KO lung compared to WT. Collectively, these data identify a previously unrecognized role for FHL2 in the pathogenesis of pulmonary granulomatous inflammation, partly through its effect on macrophage polarization, modulation of the Th1/Th2 balance and regulation of permeability in lung.